Pursuing citizenship in the enforcement era - Chen, Ming Hsu (Stanford : Stanford University Press, 2020)
"Ming Hsu Chen provides readers with the everyday perspectives of immigrants on what it is like to try to integrate into American society during a time when immigration policy is focused on enforcement and exclusion"--
Pursuing citizenship in the enforcement era -- Unequal citizenship : gaps in formal and substantive citizenship -- Tiered pathways to citizenship -- Unstable pathways to formal citizenship -- Barriers to full citizenship -- Constructing pathways to full citizenship.
Includes bibliographical references (pages 193-208) and index.
Keywords: Citizenship -- United States; Immigrants -- United States; Naturalization -- United States; Emigration and immigration law -- United States; United States -- Emigration and immigration -- Government policy